2018
DOI: 10.1051/matecconf/201816203021
|View full text |Cite
|
Sign up to set email alerts
|

Change detection and building spatial geodatabase for Iraqi marshes

Abstract: The Iraqi Marshlands has natural and economic potential through its environment rich in various forms of lives. This region has suffered numerous setbacks due to human and natural factors, especially in the last two decades of the last century, which led to significant environmental degradation. The purpose of this paper is to prepare spatial data for the area of the marshes in Iraq as a base (Hour-al Hoveizah and central marshes and Hammar). Also, the other aim is to produce a digital geodatabase for the mars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The research findings previously get a lot of weaknesses, along with a long necessary to finish and the capacity to handle places or do analyzes. With the development of advanced technology such as geospatial techniques, which already are commonly used in a number of industries [10][11][12][13][14][15][16]. According to the literature, there are no geographical control methods for agricultural lands belonged to Islamic endowments.…”
Section: Related Workmentioning
confidence: 99%
“…The research findings previously get a lot of weaknesses, along with a long necessary to finish and the capacity to handle places or do analyzes. With the development of advanced technology such as geospatial techniques, which already are commonly used in a number of industries [10][11][12][13][14][15][16]. According to the literature, there are no geographical control methods for agricultural lands belonged to Islamic endowments.…”
Section: Related Workmentioning
confidence: 99%
“…In another study, Gaar et al, 2009 [21] applied A Gaussian plume model to predict the dispersion of CO emissions of elevated flares in Basra city, their results indicated that the highest CO concentrations occur under unstable weather conditions. In general, dispersion models can be consistent with the GIS environment, another technique depends on remote sensing data such as satellite images, several studies in many applications used satellite images [21][22][23][24][25][26][27][28][29][30][31] Rajab et al, 2013 measured carbon monoxide concentrations at national level in Iraq, their method has utilized satellite data captured by Terra spacecraft with a spatial resolution (1˚x1˚), the results showed that there was a notable increase in CO concentrations over industrial and congested cities compared to rural and desert areas. In another study, Majeed al et., 2020 [33] used satellite data obtained from NASA's Global Modelling and Assimilation Office to analyse surface CO over Iraq, their long-term prediction indicated that CO concentrations reached the highest values over dense and industrial cities such as Baghdad and Basra, in addition, CO concentrations were negative with wind speed and temperature.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy of the resulting model will improve as the number of GCPs is increased [11]. The model's accuracy is also affected by how the GCPs are dispersed across the project [12]. The optimal number of GCPs for UAV mapping systems is the subject of considerable study [13,14].…”
Section: Introductionmentioning
confidence: 99%